Assessment of climate conditions of 2012–2014 and their effect on the formation of frost resistance, Myronivka`s (the Myronivka institute of wheat named after V. Remeslo), and winter hardiness of soft winter wheat - Л. О. Хоменко (Plant Varieties Studying and Protection)
Assessment of agroclimatic conditions in 2012–2014 and their effect on formation of frost resistance and winter hardiness of soft winter wheat is made. Elevated temperature conditions in autumn and disturbance of cold hardening conditions caused the formation of the highest frost tolerance and winter hardiness of winter wheat only up to -15°C. Under the new climatic conditions the modern varieties of myronivska breeding are able to realize 80–85% of the genetic potential by the property.